The Relation Among Individual and Family Risk Variables in Feeding Disorders of Middle School Children - González, L.; Hidalgo, M.; Hurtado, M.; Nova, C.; Venegas, M. (Revista de Psicología, 2002)
The present research explores the relationship between the various risk factors of anorexia nervosa. Specifically considers age, weight, height , depression, family cohesion, family conflict, family adaptability. The bivariate analyses shows the most significant correlations between self-esteem and depression (-0.728), depression and anorexia (0.710), self-esteem and anorexia (-0.699). It also appears significant the correlations between anorexia nervosa and conflict (0.406), cohesion (-0.289) and weight (0.285). In the multivariate analysis, depression, self-esteem, weight, conflict, cohesion, height and the type of high-school, predict the anorexia risk. Results and possible lines for future investigations are discussed.